High-Efficiency Polarization-Independent LCoS Utilizing a Silicon-Based Metasurface - Yuxi Deng; Boyun Liu; Jinhua Yan (Photonics)
In this paper, we propose and demonstrate a liquid crystal on silicon (LCoS) device that achieves high-efficiency, broadband, polarization-independent phase modulation by integrating a metasurface between the liquid crystal layer and the backplane of a commercial LCoS device. The metasurface is composed of rectangular silicon pillars encapsulated in silicon dioxide. By precisely adjusting the orientation and dimensions of these silicon pillars, the metasurface effectively controls the polarization state of the incident light, enabling polarization-independent phase modulation across the C+L band. Experimental results show that the polarization conversion ratio remains approximately 95% throughout the entire C+L band under varying driving voltages. Due to the low absorption characteristics of silicon and silicon dioxide, the metasurface integration introduces minimal loss. Additionally, the experimental results indicate that the reflectance of the metasurface-integrated LCoS exceeds 96% of the original LCoS reflectance. Notably, the metasurface does not affect the phase modulation characteristics of the device or exacerbate the fringing field effect, which could otherwise degrade modulation efficiency. The fabrication process for incorporating the silicon metasurface into the LCoS is fully compatible with standard semiconductor manufacturing techniques, thus facilitating the potential for large-scale production. Theoretical analysis further confirms that the design is tolerant to fabrication errors.